A rare presentation of a case of obsessive–compulsive disorder comorbid with bipolar affective disorder - Nimmy Chandran; Arpit Parmar; Koushik Sinha Deb (Indian Journal of Psychological Medicine, 2017)
Obsessive–compulsive disorder (OCD) is a chronic illness with waxing and waning course. OCD is not uncommonly found to be comorbid with bipolar affective disorder (BPAD). The course and prognosis of OCD have distinctive features in such cases. Only rarely symptoms of OCD emerge during mania in such individuals. We hereby report a very unusual case of OCD comorbid with BPAD in which obsession and compulsion symptoms occurred only during manic episodes with complete remission during periods between manic episodes (including during depressive episodes).